Multimodal MRI can identify perfusion and metabolic changes in the invasive margin of glioblastomas. Issue 2 (3rd July 2015) - Price, Stephen J.; Young, Adam M.H.; Scotton, William J.; Ching, Jared; Mohsen, Laila A.; Boonzaier, Natalie R.; Lupson, Victoria C.; Griffiths, John R.; McLean, Mary A.; Larkin, Timothy J.
Abstract : Purpose: To use perfusion and magnetic resonance (MR) spectroscopy to compare the diffusion tensor imaging (DTI)‐defined invasive and noninvasive regions. Invasion of normal brain is a cardinal feature of glioblastomas (GBM) and a major cause of treatment failure. DTI can identify invasive regions. Materials and Methods: In all, 50 GBM patients were imaged preoperatively at 3T with anatomic sequences, DTI, dynamic susceptibility perfusion MR (DSCI), and multivoxel spectroscopy. The DTI and DSCI data were coregistered to the spectroscopy data and regions of interest (ROIs) were made in the invasive (determined by DTI), noninvasive regions, and normal brain. Values of relative cerebral blood volume (rCBV), N‐acetyl aspartate (NAA), myoinositol (mI), total choline (Cho), and glutamate + glutamine (Glx) normalized to creatine (Cr) and Cho/NAA were measured at each ROI. Results: Invasive regions showed significant increases in rCBV, suggesting angiogenesis (invasive rCBV 1.64 [95% confidence interval, CI: 1.5–1.76] vs. noninvasive 1.14 [1.09–1.18]; P  < 0.001), Cho/Cr (invasive 0.42 [0.38–0.46] vs. noninvasive 0.35 [0.31–0.38]; P  = 0.02) and Cho/NAA (invasive 0.54 [0.41–0.68] vs. noninvasive 0.37 [0.29–0.45]; P  = < 0.03), suggesting proliferation, and Glx/Cr (invasive 1.54 [1.27–1.82] vs. noninvasive 1.3 [1.13–1.47]; P  = 0.028), suggesting glutamate release; and a significantly reduced NAA/Cr (invasive 0.95 [0.85–1.05] vs. noninvasive 1.19 [1.06–1.31]; P  = 0.008). The mI/Cr was not different between the three ROIs (invasive 1.2 [0.99–1.41] vs. noninvasive 1.3 [1.14–1.46]; P  = 0.68). In the noninvasive regions, the values were not different from normal brain. Conclusion: Combining DTI to identify the invasive region with perfusion and spectroscopy, we can identify changes in invasive regions not seen in noninvasive regions. J. Magn. Reson. Imaging 2016;43:487–494.